Surface deformation and strike-slip faulting controlled by dyking and host rock lithology: A compendium from the Krafla Rift, Iceland - Tibaldi A.; Bonali F. L.; Russo E.; Fallati L. (Journal of Volcanology and Geothermal Research, 2020)
In the present work, we have obtained a detailed, complete view of surface deformation at a volcano-tectonic structure belonging to the Krafla Fissure Swarm (NE Iceland), through the integration of field mapping and the Aerial Structure from Motion technique (ASfM), as well as through orthomosaics and Digital Surface Models (DSMs). The documented, 2.5-km-long deformation zone is marked by a range of features, such as topographic bulging, parallel extension fractures, and narrow grabens affected by local floor uplift, which we have explained as the effect of the northward, shallow propagation of a dyke from the Krafla magma chamber. Our lithostratigraphic field survey of the area, at a 1: 5000 scale, indicates that major changes in the pattern of surface deformation take place across the contacts between deposits with different rheological properties. The transition from very stiff lavas to softer hyaloclastites produces changes from extensional fracturing to normal faulting, though the width of the deformation zone does not change. We have also documented a number of NE-SW, left-lateral and NNW-SSE, right-lateral strike-slip fault zones that are rotated in clockwise and anticlockwise sense to the main NNE-SSW graben trend, and extend outwards as much as about 17 m. The graben zone terminates to the north by splitting into two strike-slip fault zones. These were likely generated at the front of the dyke tip during its propagation, and were later on bypassed by the advancement of the dyke. As the dyke entered the soft hyaloclastites, propagation was slowed down and the dyke became thicker.